2020
DOI: 10.21203/rs.3.rs-58822/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA RHPN1-AS1 promotes cholangiocarcinoma progression and predicts poor clinical outcome through miR-345-5p/YAP1 axis

Abstract: Background LncRNAs have proven to be involved in the initiation and progression of cholangiocarcinoma (CCA), although the mechanism by which this occurs remains unknown. Methods The current study reveals that RHPN1-AS1 was overexpressed in CCA patient samples, which predicted poor outcome of CCA patients. RHPN1-AS1 increased in vitro pancreatic carcinoma cell proliferation as well as promoted xenograft growth in vivo. Mechanistically, DANCR upregulated expression of YAP1 by competitively binding to miR-345-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These data revealed that DANCR downregulation could efficiently reduce the inflammatory response and oxidative stress during AS progression, contributing to our understanding of the pathogenic mechanism during AS development. In addition, DANCR has been identified as the ceRNA of several target miRNAs other than miR-214-5p, such as miR-185-5p [32], miR-874-3p [33], miR-1301-3p [34], miR-185-5p [35], miR-345-5p [36], miR-125b-5p [37], and miR-144-3p [38]. Since one lncRNA might target one or more downstream miRNAs [39], we hypothesized that DANCR might also have other target miRNAs that participated in the function of this lncRNA in AS progression.…”
Section: Discussionmentioning
confidence: 99%
“…These data revealed that DANCR downregulation could efficiently reduce the inflammatory response and oxidative stress during AS progression, contributing to our understanding of the pathogenic mechanism during AS development. In addition, DANCR has been identified as the ceRNA of several target miRNAs other than miR-214-5p, such as miR-185-5p [32], miR-874-3p [33], miR-1301-3p [34], miR-185-5p [35], miR-345-5p [36], miR-125b-5p [37], and miR-144-3p [38]. Since one lncRNA might target one or more downstream miRNAs [39], we hypothesized that DANCR might also have other target miRNAs that participated in the function of this lncRNA in AS progression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, RHPN1‐AS1 increased the expression of leucine zipper/EF hand transmembrane‐containing‐1 (LETM1) in ovarian cancer via inhibiting miR‐596 expression to activate the FAK/PI3K/AKT signaling pathway to promote tumorigenesis and metastasis 11 . Other studies also demonstrated the oncogenic role of RHPN1‐AS1 in cholangiocarcinoma, 12 cervical cancer, 13 colorectal cancer, 14 gastric cancer, 15 and hepatocellular carcinoma 16 . Nevertheless, the molecular mechanism of RHPN1‐AS1 regulation in PCa tumor progression remains unclear.…”
Section: Introductionmentioning
confidence: 99%